WORKING CAPITAL MANAGEMENT BEFORE AND DURING THE COVID-19 PANDEMIC AND THEIR EFFECT ON PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Shinta Heru Satoto; Hasa Nurrohim KP; Sri Budiwati WS (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to examine differences in the company's working capital management before and during the Covid-19 pandemic and to test the effect of working capital management variables on profitability. Working capital management variables used are inventory turnover, accounts receivable turnover, cash turnover, and net working capital. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. The research period was divided into 2, namely the period before the Covid-19 pandemic in 2017, 2018, and 2019, and the period during the 2020 and 2021 pandemic. The samples used were selected by purposive sampling criteria and obtained from 143 companies as samples. The results showed that there were differences in inventory turnover and receivables turnover before and during the Covid-19 pandemic. Meanwhile, cash turnover and net working capital showed no difference before and during the pandemic. The results of the influence test show that there is a significant positive effect of receivables turnover and cash turnover on profitability, while inventory turnover and net working capital do not show a significant effect on profitability.